1993
DOI: 10.1073/pnas.90.14.6889
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam dependence prevented by glutamate antagonists.

Abstract: Long-term treatment leads to tolerance to and dependence on benzodiazepines. Abrupt termination of benzodiazepine administration triggers the expression of signs of dependence. Mice withdrawn from chronic treatment with diazepam showed a time-related evolution of anxiety, muscle rigidity, and seizures between days 4 and 21 after treatment discontinuation. A period between withdrawal days 1 and 3 was symptom-free. Surprisingly, during this "silent phase" the susceptibility of mice to a-amino-3-hydroxy-5-tert-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 11 publications
6
55
0
1
Order By: Relevance
“…Similarly, following chronic ethanol administration, fast AMPA/kainate receptor-mediated CA1 neuron synaptic potentials progressively increase from 2 to 6 h after cessation of ethanol consumption (Molleman and Little, 1995). In the present study, AMPAR changes preceded NMDAR changes (Figure 3), a temporal pattern, which parallels that observed following chronic diazepam (Steppuhn and Turski, 1993). Systemic GYKI-52466 prevented both increased AMPAR-mediated excitation in CA1 neurons and withdrawal-anxiety when injected at the onset of FZP withdrawal (Figure 7a and b), while MK-801 blocked downregulation of NMDAR-mediated currents in 2-day FZP-withdrawn rats.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similarly, following chronic ethanol administration, fast AMPA/kainate receptor-mediated CA1 neuron synaptic potentials progressively increase from 2 to 6 h after cessation of ethanol consumption (Molleman and Little, 1995). In the present study, AMPAR changes preceded NMDAR changes (Figure 3), a temporal pattern, which parallels that observed following chronic diazepam (Steppuhn and Turski, 1993). Systemic GYKI-52466 prevented both increased AMPAR-mediated excitation in CA1 neurons and withdrawal-anxiety when injected at the onset of FZP withdrawal (Figure 7a and b), while MK-801 blocked downregulation of NMDAR-mediated currents in 2-day FZP-withdrawn rats.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, these changes correlated with localized increases in AMPAR-antagonist binding and decreases in NR2B subunit mRNA and protein levels in the CA1, but not CA3 or DG, region, the latter observation consistent with a decreased efficacy of NMDA applied to isolated CA1 neurons . Modulation of hippocampal glutamatergic function may be important in BZ withdrawal behaviors, as the hippocampus is an integral component of several neural circuits implicated in the expression of anxiety (Andrews et al, 1997;File et al, 1996;McNaughton and Gray, 2000;Menard and Treit, 2001;Millan, 2003) and seizures can originate in the hippocampus during BZ withdrawal (Steppuhn and Turski, 1993). In support of this possibility, Izzo et al (2001) demonstrated increased AMPAR subunit GluR1 protein in rat hippocampus, which corresponded with anxiety-like behavior in an elevated plus-maze during withdrawal from chronic diazepam.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The number of interruptions of horizontal sensors was taken as a measure of horizontal activity, whereas that of vertical sensors was taken as a measure of vertical activity. Furthermore, the time spent by mice moving in close proximity to the walls (Ͻ1 cm) or in the center (Ͼ1 cm), indicating fear, was monitored (10), and the center-time͞margin-time ratio was used as a measure of anxiety (11). Locomotor activity and movement tracking were monitored every 4 weeks in independent groups of mice for 2 min between 9 and 10 a.m. Motor Disturbances.…”
Section: Methodsmentioning
confidence: 99%